Penerapan Metode Aku Cepat Membaca (ACM) untuk Meningkatkan Kemampuan Membaca Permulaan Siswa - Rossi Dwita Pertianti; Asis Saefuddin; Sani Insan Muhamadi (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The study is motivated by the low reading ability of first-grade students at MI Al-Futuhat, where 62.5% of the students had not reached the established KKTP (≥70). This study aims to determine the students' initial reading ability before and after applying the ACM method and the learning process with the ACM method in each cycle. The ACM method integrates play, imagination, and creativity through instruments, storytelling, and music. The research uses a mixed-methods approach with the Class Action Research (CAR) method, as well as data collection techniques such as observation, performance tests, and documentation. The results show that before the ACM method's application, the classical accuracy of students' reading ability was only 37.50% ("Poor" category). After the ACM method's application, there was a significant improvement: the average student score increased from 51.56 to 67.97 in cycle I and 79.30 in cycle II. The percentage of classical accuracy increased from 37.50% to 56.25% in cycle I and 81.25% in cycle II. Student and teacher activities also increased in each cycle. With these results, learning was stopped at cycle II because the success indicator had been achieved (≥75%), reflecting the positive impact of the ACM method. This study concludes that the ACM method effectively improves students' initial reading ability and is recommended for application in teaching.